Por uma educação das relações étnico-raciais: análise afrocentrada em discursos que constituem livros didáticos de ciências naturais - Silva, Clemilson Cavalcanti da (2021)
Law n° 10.639/2003 promoted profound and necessary changes in the Law of Directives and Bases of National Education (LDB), of 1996, with regard to the debate of ethnic-racial relations in the Basic Education curriculum and, consequently, in the elaboration of the contents that are inserted in textbooks (curriculum artifact), used by Brazilian public schools. This work has as object of study textbooks of Natural Sciences that were used in public schools before and after Law n° 10.639/2003, focusing on the contents that approach the Afro-Brazilian and African population. The general objective is to understand how the discourses and images that make up Natural Sciences textbooks show the Afro-Brazilian and African population endorsed by an education in ethnic-racial relations. As a theoretical reference, we use Afrocentricity as an epistemology/paradigm that corroborates the changes that the Law aforementioned promoted in the Basic Education curriculum, particularly in the teaching of Natural Sciences. The theoretical-methodological basis to support the objective of the study is based on three moments, which actually occur simultaneously: The first, refers to the qualitative research approach; the second, relates to the technical procedures conducted by the documentary research and, lastly, in order to contribute to the construction of inferences and interpretations, the data analysis technique is evidenced, which follows the theoretical contribution of the content analysis. Provided with the theoretical-methodological framework of the research, it was possible to build interpretations and inferences that gave answers to our research objective. Thus, we point three out to exemplify the study: the books on Natural Sciences that were produced under the guidelines of the LDB, from 1971, and Technical Note 853, from the same year, which guided the curriculum, did not discuss the ethnic-racial theme in their contents. In addition, they were not concerned with reinforcing negative ethnic-racial representations of the black population; after the promulgation of the LDB in 1996 and the creation of the PCN in 1998, the textbooks on Natural Sciences, which were produced under the guidance of these legal documents, even if in an incipient way, began to change the discourse in relation to the black population, especially with regard to negative ethnic-racial representations; after the promulgation of Law n° 10.639/2003, which amended the LDB, of 1996, it is possible to note in the books on Natural Sciences, a certain care in working with contents that discuss ethnic- racial relations. However, they do not mention that Law. In addition, regardless of the historical time in which the book was written, there is a total prevalence of Europeanized references in the construction and approach of the contents. Thus, we understand that Afrocentricity is a paradigm that corroborates Law n° 10.639/2003, and a viable way to change the European hegemony in the contents and approach of Textbooks on Natural Sciences.